Artikel Pengaruh Experiential Marketing terhadap Repurchase Intention yang Dimediasi oleh Guest Satisfaction di Aston Batam Hotel & Residence (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze the impact of experiential marketing on repurchase intention, mediated by guest satisfaction at Aston Batam Hotel & Residence. The background phenomenon underlying this research is the discrepancy between the high number of guests staying and the low number of returning guests during the period from January to June 2024. Despite receiving many positive reviews, the hotel has yet to establish strong customer loyalty. This indicates a need to evaluate the hotel's marketing strategies and the guest experience it provides. A quantitative approach was adopted, employing the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. A total of 130 respondents were obtained through the distribution of questionnaires using a five-point Likert scale, measuring guest perceptions of experiential marketing, guest satisfaction, and repurchase intention. The data were analyzed using SmartPLS software to test the validity, reliability, and relationships among the structural model variables. The results of the analysis show that experiential marketing does not have a direct significant effect on repurchase intention, but it has a positive and significant effect on guest satisfaction. Furthermore, guest satisfaction is proven to have a significant impact on repurchase intention. The findings also confirm that guest satisfaction acts as a mediating variable in the relationship between experiential marketing and repurchase intention. The conclusion of this study emphasizes that guest satisfaction is a crucial factor in building customer loyalty and encouraging the intention to repurchase. Therefore, the hotel needs to enhance the quality of the customer experience holistically—not only focusing on service delivery but also creating meaningful and memorable impressions. In the highly competitive hospitality industry, delivering impactful and satisfying experiences is key to retaining customers and increasing guest retention. This study provides both theoretical and practical contributions to the development of experience-based marketing strategies and offers a deeper understanding of the role of guest satisfaction as a key driver of customer loyalty.